Implementasi pendekatan kontekstual untuk meningkatkan prestasi belajar matematika siswa - Khalid Awaluddin (JPPTK: Jurnal Pendidikan Pembelajaran & Penelitian Tindakan, 2022)
This study has a goal to improve student achievement in learning comparative mathematics in class V (five) SDN 1 Landasan Ulin Selatan. The method used in this research is the Classroom Action Research (CAR) method and is carried out in 3 cycles usin,g a contextual approach. The research was carried out in class V (five) at SDN 1 Landasan Ulin Selatan Banjarbaru with a total of 21 students in the even semester of the 2018/2019 school year. The results of the research conducted showed that the average test scores in cycles I (one) to III (three) respectively were 66.36; 72.72; 78.18. For student learning completeness in cycles I (one) to III (three) reached 66.67%, 76.19%, 85.71%. This study contains findings in the form of test averages and student learning mastery has increased and achieved individual mastery and even classical using a contextual approach.